Assasment Pengukuran Anak Berkebutuhan Khusus Secara Akademik - Ficka Ferdianti; Ruci Kurnia; Adam Sari; M. Efendi; Muhammad Hendri; Indra Boby; Opi Andriani (Student Scientific Creativity Journal, 2024)
Inclusive education is a process of responding to the diverse needs of all students. Various efforts can be made through changes and modifications in content, approaches, structures and strategies that can accommodate the needs of all students according to their age group. Implementing inclusive education requires schools to make adjustments in terms of curriculum, educational infrastructure and learning systems that are tailored to the individual needs of students, including assessing learning outcomes and determining grade promotion. The diversity of characteristics of students in inclusive schools certainly opens up opportunities for a very varied learning outcomes assessment system in determining grade promotion. The assessment system for learning outcomes for children with special needs has so far been the same as for other students. The assessment system commonly used in determining grade promotion for students in inclusive schools is based on the achievement of mental skills.